2017
DOI: 10.1021/acs.jpcc.6b10202
|View full text |Cite
|
Sign up to set email alerts
|

A Convenient Route for Au@Ti–SiO2 Nanocatalyst Synthesis and Its Application for Room Temperature CO Oxidation

Abstract: Small gold nanoparticles of size less than 5 nm encapsulated inside titanium modified silica shell have been reported. Here, a modified sol–gel method, which is a one-step process, produces Au@Ti–SiO2 nanocatalyst with a good control of titanium loading. With a titanium loading of 0.9 and 2.2 wt % in silica, unprecedented low temperature activity (full conversion) is observed for this catalyst for CO oxidation reaction compared to Au@SiO2 catalyst. A combination of optimum sized gold nanoparticles with a large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…One of the reactions that has received the most attention in the field of heterogeneous catalysis is CO oxidation [ 33 , 34 , 35 ]. Both experimental and theoretical studies have investigated the catalysis of CO oxidation by cluster [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. Payam et al [ 36 ] found that the catalytic activity of Pd/TiO 2 /Ti metal-supported catalysts was improved by the introduction of Zn, especially at Pd:Zn = 2:1, which reduced the binding energy of CO on the surface and improved the dissociative adsorption of oxygen, which facilitated the oxidation of CO.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the reactions that has received the most attention in the field of heterogeneous catalysis is CO oxidation [ 33 , 34 , 35 ]. Both experimental and theoretical studies have investigated the catalysis of CO oxidation by cluster [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. Payam et al [ 36 ] found that the catalytic activity of Pd/TiO 2 /Ti metal-supported catalysts was improved by the introduction of Zn, especially at Pd:Zn = 2:1, which reduced the binding energy of CO on the surface and improved the dissociative adsorption of oxygen, which facilitated the oxidation of CO.…”
Section: Introductionmentioning
confidence: 99%
“…This is the first report of CO oxidation using Au/POM catalysts, and their use has the potential to be extended to various gas-phase reactions. Soni et al [ 41 ] used a novel synthesis method for the preparation of Au@Ti-SiO 2 with an optimum gold NP size (3–5 nm) using the sol–gel method in one step; for Si/Ti ratios of 10 (ATS 10) and 50 (ATS 50), the activity dramatically increased after treatment in a nitrogen flow, with almost 100% conversion of CO at room temperature.…”
Section: Introductionmentioning
confidence: 99%